Guyana : Staff Report for the 2009 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2010)
Guyana has weathered the impact of the global crisis well by regional and global standards. The current account deficit declined by 5 percent of GDP (to 8.5 percent of GDP), largely led by a reduction in imports, particularly of fuel. Macroeconomic policies have remained prudent. Monetary policy tightened somewhat in 2009, supporting the decline in inflation and external stability. Structural reform has continued to focus on further reducing vulnerabilities and entrenching long-term growth. The authorities have consolidated insurance and bank supervision at the central bank.